Coffee and tea consumption in relation with non-alcoholic fatty liver and metabolic syndrome: A systematic review and meta-analysis of observational studies. Issue 6 (December 2016) - Marventano, Stefano; Salomone, Federico; Godos, Justyna; Pluchinotta, Francesca; Del Rio, Daniele; Mistretta, Antonio; Grosso, Giuseppe
Summary: Background & aims: Diet plays a role in the onset and progression of metabolic disorders, including non-alcoholic fatty liver disease (NAFLD) and metabolic syndrome (MetS). We aimed to systematically review and perform quantitative analyses of results from observational studies on coffee/tea consumption and NAFLD or MetS. Methods: A Medline and Embase search was performed to retrieve articles published up to March 2015. We used a combination of the keywords "coffee", "caffeine", "tea", "non-alcoholic fatty liver disease", "non-alcoholic steatohepatitis", "metabolic syndrome". Pooled risk ratios (RRs) and 95% confidence intervals (CIs) were calculated by random-effects model. Results: Seven studies assessed coffee consumption in NAFLD patients. Fibrosis scores were reported in four out of seven; all four studies revealed an inverse association of coffee intake with fibrosis severity, although the lack of comparable exposure and outcomes did not allow to perform pooled analysis. Seven studies met the inclusion criteria to be included in the meta-analysis on coffee consumption and MetS. Individuals consuming higher quantities of coffee were less like to have MetS (RR = 0.87, 95% CI: 0.79–0.96). However, the association of coffee and individual components of MetS was not consistent across the studies. Pooled analysis of six studies exploring the association between tea consumption and MetS resulted in decreased odds of MetS for individuals consuming more tea (RR = 0.83, 95% CI: 0.73–0.95). Conclusions: Studies on coffee and NAFLD suggest that coffee consumption could have a protective role on fibrosis. Both coffee and tea consumption are associated with less likelihood of having MetS but further research with better designed studies is needed.